PENGARUH KUALITAS PRODUK, CITRA MEREK, PERSEPSI HARGA DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK WARDAH PADA MAHASISWA UNIVERSITAS MUHAMMADIYAH PURWOKERTO - Alifa, Nadya Nur; Widyaningtyas, Dian; Rahayu, Tri Septin Muji; Haryanto, Totok (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to investigate the impact of product quality, brand image, price perception, and product design on students’ purchase decisions for Wardah cosmetics at Muhammadiyah University Purwokerto.Methods: Purposive sampling was used, with a total of 130 respondents who had purchased and used Wardah cosmetic products. Results: Product quality, price perception, and product design have a positive and significant effect on purchasing decisions. This suggests that consumers prioritize good quality, a reasonable price, and attractive product design when making purchasing decisions. Meanwhile, brand image does not have a significant effect on purchasing decisions. Although consumers have certain perceptions of the Wardah brand, its brand image is not strong enough to influence purchasing decisions. Consumers generally focus more on the direct benefits of Wardah cosmetics.Conclusion and Suggestion: This study demonstrates that companies must prioritize enhancing product quality, offering prices that align with the benefits provided, and developing more appealing product designs to influence purchasing decisions, as these factors have been proven to drive purchasing decisions. Keywords: Brand Image, Price Perception, Product Design, Product Quality, Purchase Decision,